Chemical Composition and Immunomodulatory Activity of Essential Oils from Rhododendron albiflorum - Igor A. Schepetkin; Gulmira Özek; Temel Özek; Liliya N. Kirpotina; Andrei I. Khlebnikov; Mark T. Quinn (Molecules, 2021)
Rhododendron (Ericaceae) extracts contain flavonoids, chromones, terpenoids, steroids, and essential oils and are used in traditional ethnobotanical medicine. However, little is known about the immunomodulatory activity of essential oils isolated from these plants. Thus, we isolated essential oils from the flowers and leaves of R. albiflorum (cascade azalea) and analyzed their chemical composition and innate immunomodulatory activity. Compositional analysis of flower (REOFl) versus leaf (REOLv) essential oils revealed significant differences. REOFl was comprised mainly of monoterpenes (92%), whereas sesquiterpenes were found in relatively low amounts. In contrast, REOLv was primarily composed of sesquiterpenes (90.9%), with a small number of monoterpenes. REOLv and its primary sesquiterpenes (viridiflorol, spathulenol, curzerene, and germacrone) induced intracellular Ca2+ mobilization in human neutrophils, C20 microglial cells, and HL60 cells transfected with N-formyl peptide receptor 1 (FPR1) or FPR2. On the other hand, pretreatment with these essential oils or component compounds inhibited agonist-induced Ca2+ mobilization and chemotaxis in human neutrophils and agonist-induced Ca2+ mobilization in microglial cells and FPR-transfected HL60 cells, indicating that the direct effect of these compounds on [Ca2+]i desensitized the cells to subsequent agonist activation. Reverse pharmacophore mapping suggested several potential kinase targets for these compounds; however, these targets were not supported by kinase binding assays. Our results provide a cellular and molecular basis to explain at least part of the beneficial immunotherapeutic properties of the R. albiflorum essential oils and suggest that essential oils from leaves of this plant may be effective in modulating some innate immune responses, possibly by inhibition of neutrophil migration.